Analisis Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja COBIT 5 (studi Kasus : DISKOMINFO Lombok Barat) - Irma Putri Rahayu; Nadiyasari Agitha; Moh. Ali Albar (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
Abstract Information technology governance is an integrated part of the management of organizations that govern leadership, the organization of process structure arrangements that govern information technology is used as optimally as possible. Work processes and relationships between the office community, researchers and various levels of interests and stakeholders. COBIT 5 is a company that provides services to companies, both companies, organizations, and management in managing and managing assets or IT resources to achieve company goals. It human resource in West Lombok is currently not well managed, Which hes not yet fulfilled the need for IT human resources in the office of West Lombok To solve this problem the authors carry out ITgovernance using the framework COBIT 5 On DISKOMINFO west Lombok. On DISKOMINFO West Lombok. This study will provide recommendation for improvement of IT problems the exist in diskominfo West Lombok and cand be used as a reference, especially in the managed of IT human resources and can improve the performance of DISKOMINFO west Lombok. On DSIKOMINFO West Lombok using to IT processes APO01 (management framework IT) and APO07 (human resouces). The result of this analysis are the capability level of IT governace that reflects the condition of IT governance in DISKOMINFO West Lombok. With refenace to the capability level provided by the cobit 5 framework, namely from level 1 (performed) to 5 (optimising). Key words: information technology, DSIKOMINFO COBIT 5